2015
DOI: 10.1007/s12298-015-0322-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic diversity assessment of sesame (Sesamum indicum L.) accessions differing in origin

Abstract: Sesame is an important ancient oilseed crop of high medicinal value. In the present study, 37 characters including both quantitative and qualitative traits of sixty genotypes were characterized following IPGRI morphological descriptors for sesame. Multivariate analysis was computed to distinguish the varieties into different groups. Though thirty six microsatellite markers including genomic and Est-SSR markers were initially selected, but, finally, the accessions were genotyped by eight polymorphic primers. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
5
39
3
3
Order By: Relevance
“…Each marker amplified 1 to 5 alleles with an average of 2.89 alleles per locus. The SSR markers in the present study showed a lower number of alleles than previous analysis of the diversity of sesame accessions conducted with SSR markers (Dixit et al, 2005;Gebremichaeland Parzies, 2011;Kumar and Sharma, 2011;Nweke et al, 2015;Pandey et al, 2015).…”
Section: Resultscontrasting
confidence: 77%
“…Each marker amplified 1 to 5 alleles with an average of 2.89 alleles per locus. The SSR markers in the present study showed a lower number of alleles than previous analysis of the diversity of sesame accessions conducted with SSR markers (Dixit et al, 2005;Gebremichaeland Parzies, 2011;Kumar and Sharma, 2011;Nweke et al, 2015;Pandey et al, 2015).…”
Section: Resultscontrasting
confidence: 77%
“…In an earlier study reported by Pandey et al (2015), a collection of 60 sesame genotypes including exotic collections, indigenous collections and landraces were classified based on morphological and marker analysis which served as a base population for selection of seven parents. Based on three clustering pattern and yield performance records, the seven parents namely, Gujarat Til-2 (Western India), TKG-22 (Central India), OSC-593 (South Eastern India), , , UMA (South Eastern India) and one indigenous collection, NIC-8316 (Eastern India) (Table 1) from five major sesame-growing states of India were selected for a 7 9 7 half-diallel mating design.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…DNA amplification was done in 25 μL reaction mixture that consists of 0.2 μmol L −1 SSR primers, 0.2 mM of each dNTPs, 2 mmol L −1 MgCl 2 , 1X PCR buffer and 0.5 unit Taq polymerase, and 50 ng sample DNA. The procedures for SSR and Est-SSR were performed on a DNA thermocycler kit (Eppendorf AG 6321, Germany) as described by Pandey et al (2015). 3% agarose gel (Sigma USA) was used for separating the amplified PCR products.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Microsatellites or simple sequence repeat (SSR) is considered a good choice because of high abundance and reproducibility, easy scoring, low cost, extensive coverage, high polymorphic information content (PIC)and its co dominant nature (Wei et al,2014;Pandey et al, 2015;Dossa et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%